2013
DOI: 10.1080/13548506.2013.859712
|View full text |Cite
|
Sign up to set email alerts
|

A more global approach to musculoskeletal pain: Expressive writing as an effective adjunct to physiotherapy

Abstract: The aim of this study was to investigate the effects of written emotional disclosure as an adjunct to physiotherapy. Forty outpatients with musculoskeletal pain were treated with Mézières physiotherapy for 10 sessions. Half of the subjects also wrote about difficult life experiences immediately after four of these sessions. Data analysis showed that although both the writing and non-writing groups displayed lower pain scores after physiotherapy, the difference was stronger in the writing group. Pain scores con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Psychosocial risk factors include catastrophizing, fear avoidance, magnification, depression, and anxiety [30]. At-risk patients underwent education on expressive writing and cognitive behavioral techniques [31]. Group mindfulness classes were also encouraged in patients who were thought to exhibit psychosocial risk factors.…”
Section: Ipu Modelmentioning
confidence: 99%
“…Psychosocial risk factors include catastrophizing, fear avoidance, magnification, depression, and anxiety [30]. At-risk patients underwent education on expressive writing and cognitive behavioral techniques [31]. Group mindfulness classes were also encouraged in patients who were thought to exhibit psychosocial risk factors.…”
Section: Ipu Modelmentioning
confidence: 99%
“…To address the impact of unresolved stressful life experiences or psychological conflicts on chronic pain, we and others have tested whether reversing emotional avoidance or inhibition by privately writing or speaking about stressors will reduce pain. Trials of expressive writing or emotional disclosure have found mixed results: there have been inconsistent, often null effects for people with rheumatoid arthritis (68)(69)(70)(71)(72)(73), but some benefits for those with FM (74,75), pelvic pain (76), and musculoskeletal pain (77,78). Our review of this literature concluded that these techniques may be more helpful in patients with centralized pain than those with nociceptive pain conditions, such as rheumatoid arthritis, perhaps because of the higher levels of life stress and emotional problems in patients with centralized pain compared to RA (79).…”
Section: Expressive Writing / Emotional Disclosurementioning
confidence: 99%
“…Hence, the right thing to do might be to seek how to best combine the two paradigms in a way that maximizes the expected positive effects. Working on an integrative approach is relevant as a very recent study on chronic pain patients showed greater efficiency of physiotherapy when combined with expressive writing (Pepe et al, 2014). Our first results thus pave the way for addressing numerous variations and/or additional issues in future research on emotional disclosure.…”
Section: Discussionmentioning
confidence: 99%